Fancy Nancy tea parties - O'Connor, Jane.; Preiss-Glasser, Robin (New York : Harper, 2009)
In her own inimitable style, the girl who loves to use fancy words provides tips on how to host the perfect tea party, describing how to behave, food and drinks to serve, games to play, and much more.
Keywords: Tea -- Juvenile literature; Parties -- Juvenile literature; Afternoon teas -- Juvenile literature; Entertaining -- Juvenile literature; Children's parties -- Juvenile literature